The National SOM Survey 1996 - SOM Institute, University of Gothenburg (University of Gothenburg, 2011)
Since 1986 the research project ´Samhälle Opinion Massmedia´ (SOM) has been carrying out an annual nation-wide survey of Swedish opinions. This is accordingly the eleventh survey in this series. The questionnaire was divided into six subject fields: mass media; politics and society; Sweden´s relations to the rest of the world; energy, nuclear power and environment; leisure; and background. Most of the questions are replications of questions asked in one or several previous SOM-surveys. New media questions dealt with how often the respondent read local advertisement papers as well as daily papers on the internet. The respondent also had to state if a number of statements corresponded with qualities held by the morning and evening papers the respondent used to read, and to indicate if criticism directed towards daily papers could be applied on papers read by the respondent. Respondents were also asked about their opinion on the function of democracy in Sweden, attitudes towards proposals how to reduce unemployment, and to give their opinion on the possibility to reduce unemployment by 50 percent until year 2000. Furthermore the respondents had to rank the most important and second most important goals for Sweden to work towards during the coming ten years. Respondents were also asked if they could consider to undertake political assignments for the political party they sympathize with. Other questions dealt with qualities possessed by three different political parties and their party leaders as well as by three different mass media; attitudes towards referendum held in certain issues as well as general attitudes toward referenda; and different group´s influence on programs supplied by the non commercial television channels as well as the commercial channel TV4. Respondents had to state if they believed one in general can trust most people, they also had to tell how satisfied they were with their own life, and to tell their knowledge of foreign languages.

Purpose:

The main purpose of the surveys is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den elfte undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

1996 års undersökning består av sex sammanhållna delar: massmedier; politik och samhälle; Sveriges förhållande till omvärlden; energi, kärnkraft och miljö; fritid; samt bakgrundsfrågor. Genom att frågor ställts på ett likartat sätt över tid finns det i SOM-serien tidsserier om bland annat medieanvändning, politik, kärnkraftsopinion och förtroende för olika samhällsinstitutioner och grupper.

Nya mediefrågor behandlar bland annat läsning av lokala annonsblad och tidningsläsning på internet; egenskaper hos de morgon- och kvällstidningar som respondenten läser och huruvida den kritik som riktats mot morgon- och kvällspress är tillämpbar på de tidningar respondenten brukar läsa. Andra nya frågeställningar berörde åsikten om hur demokratin fungerar i Sverige; åsikter om hur arbetslösheten kan minskas; och inställning till möjligheten att halvera arbetslösheten till år 2000. Därutöver fick respondenten ranka vilka mål som Sverige bör arbeta mot de kommande tio åren: upprätthålla lag och ordning; ge enskilda människor större möjlighet att påverka politiska beslut; bekämpa prisstegringarna; eller skydda yttrandefriheten. Andra frågor berörde respondentens benägenhet att åta sig politiska uppdrag; egenskaper hos tre olika partier och dess partiledare samt hos tre olika medier; åsikter om folkomröstningar i olika specifika frågor samt om folkomröstningar mera allmänt; olika gruppers inflytande på vilka program som sänds i Sveriges Television respektive TV4; samt respondentens språkkunskaper. Därutöver fick respondenten ange om man i allmänhet kan lita på de flesta människor eller om man bör vara försiktig i kontakten med andra och hur nöjd man på det hela taget är med det liv man lever.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 1996
Riks-SOM 1996
Keywords: mass media; massmedia; population migration; migration; energy; energi; environment; miljö; unemployment; arbetslöshet; european union; europeiska unionen; political interest; politiskt intresse; local government services; kommunal service; nuclear energy; kärnkraft; newspaper readership; tidnings läsekrets; membership; medlemskap; newspaper press; nyhetspress; television channels; tv-kanaler; languages; språk; television advertising; tv-reklam; news; nyheter; television news; tv-nyheter; television programmes; tv-program; energy policy; energipolitik; radioactive wastes; radioaktivt avfall; journalism; journalistik; risk; risk; referendums; folkomröstningar; financial markets; finansmarknad; terrorism; terrorism; internal politics; inrikespolitik; political parties; politiska partier; political leaders; politiska ledare; clubs; föreningar; leisure time activities; fritidsaktiviteter; refugees; flyktingar; public health risks; hälsorisker; wind energy; vindenergi; environment policy; miljöpolitik; radio listening; radiolyssnande; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap